2009
DOI: 10.1109/tns.2009.2030191
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Timing and Position Resolution Studies With 16-Pixel Silicon Photomultiplier Matrices for Small Animal PET

Abstract: A high resolution small animal PET scanner that employs Silicon Photomultiplier (SiPM) matrices as photodetectors is under development at the University of Pisa and INFN Pisa. The first SHIM matrices fabricated by the Center for Scientific and Technological Research, FBK-irst (Trento, Italy), are being evaluated for this purpose. The devices are composed of 16 (4 x 4) pixel elements of 1 mm x 1 mm in a common substrate. The first tests have been carried out employing the ASIC MAROC2 for the readout. Energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…When coupled to a scintillating medium, these devices have been used in a variety of radiation detection and spectroscopy applications including dosimetry [3,4], medical imaging [5][6][7][8], high-energy physics [9][10][11], and homeland security [12][13][14]. Additionally, organic crystals with pulse shape discrimination (PSD) capabilities coupled to SiPMs have been shown to be capable of fast-neutron detection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…When coupled to a scintillating medium, these devices have been used in a variety of radiation detection and spectroscopy applications including dosimetry [3,4], medical imaging [5][6][7][8], high-energy physics [9][10][11], and homeland security [12][13][14]. Additionally, organic crystals with pulse shape discrimination (PSD) capabilities coupled to SiPMs have been shown to be capable of fast-neutron detection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The high timing resolution (t) we expect will be used to perform the event TOF (Time Of Flight) so as to increase the SNR (Signal to Noise Ratio). In the framework of the INFN DASiPM (Development and Application of SiPMs) project we have deeply characterized both single elements SiPMs of different producers and matrices, and we have demonstrated that their characteristics in terms of energy resolution (below 15% FWHM), spatial resolution (0.9 mm FWHM) and time resolution (around 100 ps sigma for a single 3x3 mm 2 SiPM coupled to LSO:Ce,Ca) [1], [2] fulfill our requirements. In addition we have already developed a dedicated front-end in order to manage signals from SiPM matrices without degrading their large dynamic range [3].…”
Section: Introductionmentioning
confidence: 86%
“…However, PMTs have severe drawbacks, they are sensitive to magnetic fields and are expensive [1]. With the maturity of CMOS technologies, parallel combinations of passively quenched single photon avalanche diodes (SPADs) have been explored as replacements for the PMTs as photodetectors in nuclear applications and are known as silicon photomultipliers (SiPM) [1][2][3][4]. SiPMs have some advantages over PMT based detectors.…”
Section: Introductionmentioning
confidence: 99%